Scepticism About Other Minds: Propositional and Objectual - Raja Bahlul (14779609) (2023)
In this paper, I distinguish between two kinds of knowledge of other minds: a propositional kind, whereby one may say, for example, that “We can see that he is in pain,” and an objectual (object-related) kind which seems to be presupposed by knowledge claims about, for example, his present feeling of pain. I will suggest that two sceptical problems arise in connection with these two kinds of knowledge, respectively. The burden of my argument will be to show that while scepticism about propositional knowledge may be amenable to a satisfactory solution, the only route to take with scepticism about objectual knowledge is dissolution. Other Information Published in: Philosophical Investigations License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/phin.12322